2022
DOI: 10.3390/su141912530
|View full text |Cite
|
Sign up to set email alerts
|

A Mini-Review: Biowaste-Derived Fuel Pellet by Hydrothermal Carbonization Followed by Pelletizing

Abstract: This review article focuses on recent studies using hydrothermal carbonization (HTC) for producing hydrochar and its potential application as a solid fuel pellet. Due to the depletion of fossil fuels and increasing greenhouse gas (GHG) emissions, the need for carbon-neutral fuel sources has increased. Another environmental concern relates to the massive amount of industrial processing and municipal solid waste, which are often underutilized and end up in landfills to cause further environmental damage. HTC is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 74 publications
0
9
0
2
Order By: Relevance
“…However, there are few studies on the influence of holding time on the aromatization mechanism in hydrothermal carbonization and the chemical structure change of hydrothermal carbonization product-hydrochar. According to previous literature, other working conditions such as temperature can well increase the aromaticity and calorific value of hydrochar, nonetheless there is little research on the holding time [8,9,12,20]. On one basis, this paper discusses the influence of different holding time on aromaticity and calorific value, as well as the changes of physicochemical properties and aromatization mechanism of hydrochar, so as to provide theoretical basis for the research and development of efficient carbon aromatization system.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…However, there are few studies on the influence of holding time on the aromatization mechanism in hydrothermal carbonization and the chemical structure change of hydrothermal carbonization product-hydrochar. According to previous literature, other working conditions such as temperature can well increase the aromaticity and calorific value of hydrochar, nonetheless there is little research on the holding time [8,9,12,20]. On one basis, this paper discusses the influence of different holding time on aromaticity and calorific value, as well as the changes of physicochemical properties and aromatization mechanism of hydrochar, so as to provide theoretical basis for the research and development of efficient carbon aromatization system.…”
Section: Introductionmentioning
confidence: 97%
“…There is also Brauns lignin, named after Brauns, which is now believed to be part of the original lignin. Freudenberg calls it "soluble lignin" [6,[8][9][10][11][12][13][14].The term lignin now generally refers to the lignin products, which can be separated from plants as well as lignin derivatives.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the nutrients are also dissolved and found in the liquid phase. During the HTC process, the material and water are carbonized at relatively low temperatures (180-260 • C) and with a pressure rate of 2-6 MPa [6,7]. Because the material does not need to be dried before the HTC process, the technology is suitable for handling sludge.…”
Section: Introductionmentioning
confidence: 99%
“…Saqib [27] used molasses as a binder with hydrochar and pelletized these in a single pellet press and concluded that molasses played an important role when formatting pellets. Few studies on hydrochar pellets have been performed, and Gallant [7] discussed in their mini-review die temperatures, moisture contents, applied pressure, and types of binders when pelletizing hydrochar and found some recommendations related to pelletizing parameters of hydrochar. However, the experimental investigations behind recommendations are based on single pellet press techniques [6,7,23], and it has been shown that it is difficult to evaluate results between different single pellet press studies because inlet data in these studies often vary [28].…”
Section: Introductionmentioning
confidence: 99%